2008
DOI: 10.1371/journal.pone.0003879
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Uptake, Activation, and IL-23 Production by Pulmonary Myeloid DCs Drives Airway Hyperresponsiveness in Asthma-Susceptible Mice

Abstract: Maladaptive, Th2-polarized inflammatory responses are integral to the pathogenesis of allergic asthma. As regulators of T cell activation, dendritic cells (DCs) are important mediators of allergic asthma, yet the precise signals which render endogenous DCs “pro-asthmatic”, and the extent to which these signals are regulated by the pulmonary environment and host genetics, remains unclear. Comparative phenotypic and functional analysis of pulmonary DC populations in mice susceptible (A/J), or resistant (C3H) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 77 publications
5
84
0
Order By: Relevance
“…In the current study, both mDCs and pDCs were detected in the lungs of normal neonatal mice, although mDCs were typically more abundant than pDCs. We previously demonstrated that the numbers of mDCs present typically exceed pDCs by 10-25-fold in the adult mouse lung (58). Thus, in neonatal mice, the lung appears to be a more tolerogenic environment, capable of promoting the development of T regulatory rather than activated T effector cells.…”
Section: Role Of Foxa2 In the Regulation Of Pulmonary Dcsmentioning
confidence: 96%
“…In the current study, both mDCs and pDCs were detected in the lungs of normal neonatal mice, although mDCs were typically more abundant than pDCs. We previously demonstrated that the numbers of mDCs present typically exceed pDCs by 10-25-fold in the adult mouse lung (58). Thus, in neonatal mice, the lung appears to be a more tolerogenic environment, capable of promoting the development of T regulatory rather than activated T effector cells.…”
Section: Role Of Foxa2 In the Regulation Of Pulmonary Dcsmentioning
confidence: 96%
“…4G). Once recruited, CCR7 + cells migrate out of the lung and into the lymph nodes (19,20). At the same time, there was an increase in Treg-promoting factors (IL-2 and TGF-b).…”
Section: Discussionmentioning
confidence: 99%
“…T+P-induced Tregs and suppression of AAD were associated with reductions in the number of DCs containing OVA in the MLNs and lung. This may be because T+P-induced Tregs induce Fas-Fas ligandmediated or perforin-dependent killing of DCs in the lung, leading to reduced numbers of DCs carrying OVA in the MLNs (20,41). Therapeutic inhibition of DCs in AAD has been reported previously and proposed as a potential treatment for asthma (43).…”
Section: Pulmonary Cd11cmentioning
confidence: 95%
See 1 more Smart Citation
“…Environmental allergens such as house dust mite (HDM) causes lung eosinophilia (2). Followed by activation of lung epithelial cells and subsequent release of alarmins such as thymic stromal lymphopoietin (TSLP), IL-25 and IL-33 (3,4), dendritic cells (DCs) and B cells participate to prime naïve CD4 T cells to differentiate them into Th2 effector cells to secrete Th2 cytokines (IL-4, IL-5 and IL-13) and to produce B cell-mediated humoral immune responses by Ig (immunoglobulin)-E (5,6). Recently platelets were shown to participate in HDM-induced asthma stimulating Th2 cell differentiation (7).…”
mentioning
confidence: 99%